Prophetism and Enigma in the Proverbs of Zviad Gamsakhurdia - Kiria, Nana (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
The aim of the research is to critically analyze the proverbs of the great Georgian figure, thinker and writer Zviad Gamsakhurdia, in particular, fables (from a prophetic and enigmatic point of view). The research method is comparative. In comparison, the merits and weaknesses of Gamsakhurdia's works can be clearly seen, more - the first. The result of the research - Zviad Gamsakhurdia's fables are not distinguished by epicness and greatness, but contain the key to the essential ideas and principles of the writer's life. Zviad Gamsakhurdia's fables are lexically and thematically modernized and it should have been, but he carefully defends fable-Arak moderation and ideas. A proper understanding of his creativity requires an accurate understanding of in-depth semantics and stylistic features. Without freedom one cannot understand the irrationality of the existence of evil in the divine world. Freedom is not created because it is not nature, freedom precedes the universe.